Multi-therapeutic effects of human adipose-derived mesenchymal stem cells on radiation-induced intestinal injury - Chang, P (Nature Publishing Group, 2013)
Radiation-induced intestinal injuries (RIII) commonly occur in patients who suffer from pelvic or abdominal cancer. However, current management of these injuries is ineffective. Recently, mesenchymal stem cells (MSCs) have been extensively used in regenerative medicine and have achieved a high level of efficacy. In the present study, we hypothesised that human adipose-derived mesenchymal stem cells (hAd-MSCs) could be used as potential tools to heal RIII. We observed that adult Sprague–Dawley rats that received whole-abdominal irradiation benefitted from hAd-MSC injection. hAd-MSCs had RIII-healing effects, including anti-inflammation, neovascularisation and maintenance of epithelium homeostasis, as indicated by elevated serum IL-10, upregulation of vascular endothelial growth factor, basic fibroblast growth factor and epidermal growth factor in irradiated intestine, mobilisation of CD31-positive haematopoietic stem cells or haematopoietic progenitor cells, and the prolonged presence of Bmi1-positive cells within crypts. Consequently, after hAd-MSC treatment, irradiated rats survived longer than non-treated animals. These results suggest that hAd-MSCs have therapeutic potential for RIII management.